Influence of various environmental factors on the growth of children and adolescents in Jeddah, Kingdom of Saudi Arabia - Al-Agha, Abdulmoein Eid; Adam, Alyaa; Almaghrabi, Anhar; Zainalabidin, Asmaa; Ahmed, Hajar Mohammed; Almuwallad, Rawan A.; Aljahdali, Shaima H.; Alharbi, Shuruq; Alhowig, Wijdan (Acta Biomedica Atenei Parmensis, 2020)
Objectives: To evaluate the association between various environmental factors and the anthropometric measurements of children and adolescents. Methods: This retrospective studywasperformed from September 2017 to April 2018 and included 393 children aged 2-18 years. Data were extracted through patient and/or parentinterviews and from medical records of endocrine ambulatory clinics. Results: Among underweight children,the proportion of mixed-fed children was the highest, and among normal weight children, most were either bottle-fed or mixed-fed. Most overweight children were mixed-fed, and most obese children were breastfed. Underweight status was noted most commonly in children playing videogames for <2 hours/day, followed by those playing>4 and 2-4 hours/day. Normal weight was noted most commonly in those playing for >4 hours/day, followed by those playing <2 and 2-4 hours/day. Overweight status was noted most commonly in those playing videogames for >4 hours/day, followed by those playing 2-4 and <2 hours/day. Most children playing videogames for <2 hours/day were obese. Mean BMIs were the highest in those who exercised 1-2 times/week. P-values for the association between passive smoking indoors and BMI, weight, and height were 0.045, 0.150, and 0.854, respectively. Regarding socioeconomic status, log BMI values were 1.22, 1.23, and 1.26 in low-, medium-, and high-income families, respectively (P-value, 0.001). Conclusion: Children who were bottle-fed in their first year of life, played video games >2 hours/day, did not exercise regularly, were exposed to indoor passive smoking, and had a high socioeconomic status had a higher BMI and weight than their counterparts. (www.actabiomedica.it)